HUBUNGAN KECANDUAN GAME ONLINE DENGAN PENYESUAIAN SOSIAL PADA REMAJA DIDESA DUNGGALA KABUPATEN BONE BOLANGO - Liputo, Salahuddin; Ntobuo, Fendi; Basara, Yuliyanti (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2022)
Adolescence is a transitional period between childhood to adulthood. At this time, adolescents experience development to reach physical, mental, social and emotional maturity. At this time the emotional state of adolescents is still unstable because it is closely related to hormonal conditions. Adolescent emotions dominate and control themselves more than realistic thoughts (Hurlock, 1980) in (Surbakti, 2017). This research was conducted in Dunggala Village, Bonebolango District, with the objectives (1) To determine the level of addiction to online games in adolescents in Dunggala Village. , (2) To determine social adjustment in adolescents in Dunggala Village, (3) To determine the relationship between online game addiction and social adjustment in adolescents in Dunggala Village. This research uses quantitative methods. The research subjects were 50 respondents who were selected using purposive sampling. In collecting data, researchers use a scale. Data analysis in this study used the Compare means test for linearity and simple linear regression analysis. The results of the research conducted found that (1) the level of online game addiction among adolescents in Dunggala Village was in the moderate category with a percentage of 66% (33 people) while ( 2) the level of social adjustment for adolescents in Dunggala Village is also in the moderate category with a percentage of 70% (35 people). (3) It is also known (F= 3.464 with p = 0.003 and R^2 = 0.016), which means that there is a significant relationship between online game addiction and social adjustment in adolescents in Dunggala Village, Bone Bolango Regency.